Implementation Of The Inquiry Learning (Il) Model In Islamic Religious Education And Ethics Subjects Class VI In UPTD SDN 06 Guguak VIII Koto - Zainur Huda; Rifka Haida Rahma; Adi Warma (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The learning process of Islamic Religious Education and Ethics in elementary schools requires innovation that can improve the quality of education, one of which is through the application of the Inquiry Learning (IL) model. This study aims to examine the effect of the Inquiry Learning model on teacher competence, student interest and motivation to learn, and the achievement of learning outcomes in grade VI students at UPTD SDN 06 Guguak VIII Koto. Although many previous studies have examined the application of IL, there has been no research that specifically links IL with improving learning outcomes of Islamic Religious Education and Budi Pekerti in elementary schools. The methodology used in this research is quantitative and qualitative approaches through Classroom Action Research (PTK). The results showed a significant increase in student learning outcomes, with pre-cycle learning completeness of 44.44%, cycle 1 of 55.56%, cycle 2 of 66.67%, and cycle 3 of 88.89%. The application of the Inquiry Learning model proved effective in improving students' competence in the field of Islamic Religious Education and Ethics, as well as increasing their learning motivation. This research has important implications in the application of the IL model as an alternative to improve the quality of learning in elementary schools.